Genetic and Environmental Transmission of Body Mass Index Fluctuation - Bergin, Jocilyn E. (2012)
OBJECTIVE: This study sought to determine the relationship between BMI fluctuation and cardiovascular disease phenotypes, diabetes, and depression and the role of genetic and environmental factors in individual differences in BMI fluctuation using the extended twin-family model (ETFM). STUDY DESIGN AND METHODS: This study included 14,763 twins and their relatives. Health and Lifestyle Questionnaires were obtained from 28,492 individuals from the Virginia 30,000 dataset including twins, parents, siblings, spouses, and children of twins. Self-report cardiovascular disease, diabetes, and depression data were available. From self-reported height and weight, BMI fluctuation was calculated as the difference between highest and lowest BMI after age 18, for individuals 18–80 years. Logistic regression analyses were used to determine the relationship between BMI fluctuation and disease status. The ETFM was used to estimate the significance and contribution of genetic and environmental factors, cultural transmission, and assortative mating components to BMI fluctuation, while controlling for age. We tested sex differences in additive and dominant genetic effects, parental, non-parental, twin, and unique environmental effects. RESULTS: BMI fluctuation was highly associated with disease status, independent of BMI. Genetic effects accounted for ~34% of variance in BMI fluctuation in males and ~43% of variance in females. The majority of the variance was accounted for by environmental factors, about a third of which were shared among twins. Assortative mating, and cultural transmission accounted for only a small proportion of variance in this phenotype. CONCLUSIONS: Since there are substantial health risks associated with BMI fluctuation and environmental components of BMI fluctuation account for over 60% of variance in males and over 50% of variance in females, environmental risk factors may be appropriate targets to reduce BMI fluctuation.